2006
DOI: 10.1016/j.rmedu.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Smoking related COPD and facial wrinkling: Is there a common susceptibility?

Abstract: Background: Cigarette smoking causes accelerated facial wrinkling and predisposes to chronic obstructive pulmonary disease (COPD). However, it has long been recognised that there is a subgroup of susceptible smokers who are at increased risk of developing airflow obstruction. We have tested the hypothesis that there is a common susceptibility for the development of COPD and facial wrinkling in cigarette smokers. Methods: One hundred and forty nine current and ex-smokers were recruited from a family based study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Our findings corroborate and extend previous studies on the association between skin and lung aging (Lange and Schnohr, 1994;Patel et al, 2006). In contrast to previous findings, we could not show that the association between skin and lung aging is smoking dependent.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings corroborate and extend previous studies on the association between skin and lung aging (Lange and Schnohr, 1994;Patel et al, 2006). In contrast to previous findings, we could not show that the association between skin and lung aging is smoking dependent.…”
Section: Discussionsupporting
confidence: 86%
“…This assumption might be particularly true for organs that age as a consequence of extrinsic factors and cellular mechanisms that they hold in common with skin aging. In support of this concept, two previous studies (Lange andSchnohr, 1994 andPatel et al, 2006) showed that there is a smoking-dependent association between skin wrinkling and airflow obstruction of the lung, characteristic aging features of these two organs, respectively. They further suggested that pronounced skin wrinkling might be a marker for an underlying susceptibility for the effect of smoking on airflow obstruction.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…29 A recent work by Patel et al demonstrated a correlation between cutaneous aging in smokers and COPD. 30 Future studies would verify, if the presence of APAA could be a marker for predisposition to systemic damage by smoke as for early cutaneous aging.…”
Section: Discussionmentioning
confidence: 98%
“…The interplay of associated comorbidities in the causation of facial wrinkling is also reported in the literature. 20,21 Various studies on the influence of personal habits and behaviors (sunlight exposure, cigarette smoking, alcohol and coffee consumption, and cleaning teeth) on facial wrinkles show discrepancies in results. 16,17,22 In the present study, exposure to the sunlight had a significant association with wrinkling score.…”
Section: Multivariate Logistic Regressionmentioning
confidence: 99%